Repeatable and metal-independent nanotransfer printing based on metal oxidation for plasmonic color filters. Issue 23 (1st May 2019) - Hwang, Soon Hyoung; Zhao, Zhi-Jun; Jeon, Sohee; Kang, Hyeokjung; Ahn, Junseong; Jeong, Jun Ho
Abstract : A repeatable metal-independent transfer printing method is developed to repeatedly transfer nanopatterns for fabricating plasmonic color filters. Abstract : Many recently developed nanotransfer printing techniques have received much attention because of their simplicity and low cost. In addition, such techniques are suitable for fabricating nano/microscale sensors, optical elements, and electrical devices. However, conventional nanotransfer printing methods are time-consuming, cannot be easily used over large areas or with several different materials, and are not suitable for repeatedly transferring various materials onto the same substrate or a curved surface. Herein, a new nanotransfer printing method is introduced based on the oxidation of various metals and the formation of covalent bonds between spin- and spray-coatable adhesives and the chosen metal at low temperatures. These strong covalent bonds allow the fast transfer of the deposited materials from a polymer stamp without additional processing. A major advantage of this process is that it is metal-independent; nanowires of various metals are successfully transferred from the polymer stamp because strong covalent bonds form instantaneously between the metal and an adhesive-coated substrate. Moreover, this nanotransfer process can be used repeatedly to fabricate large-scale color filters from smaller areas of nanowires, regardless of the metal type and nanostructure orientation. Furthermore, plasmonic color filters composed of nanohole arrays can be obtained on both flat and curved surfaces.